The Role of Socialization in Improving the Quality of Education in the Digital Age of Village - Baiq Zil An’gina Maulida; Evi Sakina; Linda Aulia; Rabiyatul Adawiyah; Wisnu Hidayat; Rohini Rohini (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Education is an important part of human life. Without realizing it, this life is never separated from what is called education. Education is not only a transfer of knowledge, but with education we can develop good personality and character. This socialization activity aims to educate, increase insight, and knowledge for the millennial generation, especially for children and people who have minimal knowledge about education. This socialization also aims so that the community, especially schools and parents, can respond to technological developments positively so that they reflect the value of character education. The use of digital media in the learning process is a must to support the learning process carried out by teachers today. In fact, based on several research results, it is known that there are still many teachers who have not utilized digital media in the learning process they guide, as a result, students' interest in learning is low. The socialization activity was attended by the village head, school principal, teachers, community leaders and youth organizations and other people who had the opportunity to attend. With this socialization activity, it is hoped that there will be awareness and motivation for all children in the village of North Surabaya to continue their education to a higher level and awareness of parents/guardians about the importance of education in order to grow a quality generation as the successor to the nation, provide a role as a social function in society, and bring progress to the village amidst increasingly sophisticated technological developments.